A organização social e o acesso à cultura: o caso das bibliotecas parque do Estado do Rio de Janeiro - Zugliani, Luiz Fernando (2016)
This dissertation seeks to analyze the contribution of Social Organizations to cultural rights access, based on the experience of Libraries Park of the State of Rio de Janeiro, especially those located in Manguinhos and Rocinha. Aware that forms of cooperation to the realization of cultural rights are manifold and need to be designed from the interrelation of various players and aspects, all invariably need to flow into management frames that enable the access to culture. The research adopts the case study method, making use of bibliographic, documentary and field research. These findings introduce the construction scenario of cultural rights to a large expansion in Brazil, and highlight that to materialize them, it is necessary to study, evaluate and adopt alternative rather than traditional organizational characterizing the direct and indirect public administration. This document addresses the field of management and cultural rights in the context of the three major reforms of the Republican State apparatus, which occurred in the 30, 60 and 90, with emphasis on the latter, which incorporates the theory of New Public Management, the basis of this thesis. Focus is on the OS as an optional model for the management of cultural facilities, from the existing reality, motivations, strengths and perspectives and adds a narrative about the design process of the laws of the State of Rio de Janeiro. The research checks how these cultural facilities emerged and how the network formation of Park Libraries occurred. It describes the process of implementation of the Culture Social Organizations in the state and has the manager of libraries and their relationship with the Secretariat of Culture. It concludes that there is need to improve management mechanisms, so that the model can, in fact, provide contribution to access to cultural rights.